2015
DOI: 10.1007/s12035-015-9396-7
|View full text |Cite
|
Sign up to set email alerts
|

Colistin-Induced Apoptosis of Neuroblastoma-2a Cells Involves the Generation of Reactive Oxygen Species, Mitochondrial Dysfunction, and Autophagy

Abstract: Neurotoxicity remains a poorly characterized an adverse effect associated with colistin therapy. The aim of the present study was to investigate the mechanism of colistin-induced neurotoxicity using the mouse neuroblastoma-2a (N2a) cell line. Colistin induced apoptotic neuronal cell death in a dose dependent manner (colistin at 0-200 μM). Colistin treatment (at 50, 100 and 200 μM) for 24 h, significant increased the reactive oxygen species (ROS) levels; while a concomitant decrease in the activities of SOD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 49 publications
6
54
0
Order By: Relevance
“…Associated with colistin therapy, nephrotoxicity and neurotoxicity remain poorly characterized adverse effects. In terms of the relationship of colistininduced neurotoxicity and p53, Dai et al reported that the gene expression of p53, Bax, and caspase-8 significantly increased in the model of colistin-induced neurotoxicity using the mouse neuroblastoma 2a (N2a) cell line (all P values of Ͻ 0.01) (7). A recent study has shown that p53 plays a pathological role in the progression of colistin-induced apoptosis in PC-12 cells (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associated with colistin therapy, nephrotoxicity and neurotoxicity remain poorly characterized adverse effects. In terms of the relationship of colistininduced neurotoxicity and p53, Dai et al reported that the gene expression of p53, Bax, and caspase-8 significantly increased in the model of colistin-induced neurotoxicity using the mouse neuroblastoma 2a (N2a) cell line (all P values of Ͻ 0.01) (7). A recent study has shown that p53 plays a pathological role in the progression of colistin-induced apoptosis in PC-12 cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, its clinical use is limited by potential nephrotoxicity and neurotoxicity (4,5), the mechanisms of which are still unknown. It has been discovered in a mouse model and neuroblastoma 2a cells that autophagy is involved in colistin-induced nephrotoxicity (6,7). Apoptosis and autophagy are two common forms of cell death (8,9).…”
mentioning
confidence: 99%
“…All reactions were conducted in triplicate. β-actin was used as an internal control, and fold change in gene expression was calculated using the threshold cycle method (2 −ΔΔ CT ) [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was examined by using MTT method according to the previous study [ 49 ]. In brief, cells were (2–5 × 10 4 ) seed into 96-well plates.…”
Section: Methodsmentioning
confidence: 99%